Optimalisasi Sistem Informasi Sertifikasi Kompetensi Mahasiswa Manajemen di Universitas Negeri Semarang - Athoillah Athoillah; Fitrarena Widhi Rizkyana; Richatul Jannah; Aulia Prima Kharismaputra (Universitas Negeri Semarang, 2023)
Competency certification is required as a form of recognition for workers who have the skills, knowledge, and work attitudes according to the required work competency standards. Thus, the certificate holder will guarantee his credibility in carrying out the work that is his duty and responsibility. Some of the other benefits obtained by certificate holders are increasing their self-confidence, increasing sales points in labor recruitment, greater career opportunities, having clear parameters of the skills and knowledge possessed. Considering that the benefits of competency certification are considered positive, especially for students, the Management Department of the Faculty of Economics UNNES implements a competency certification program for its students. There are many competency certification options provided for FE UNNES Management Department students, including the following: (1) HR Management Student Certification; (2) Marketing Management Student Certification; (3) Financial Management Student Certification. it is expected to be able to solve problems that occur and bring benefits to optimizing student understanding of competency certification as a certificate accompanying a diploma which they will later need when applying for a job.